DECISION SUPPORT SYSTEM FOR HOME SURGERY ASSISTANCE RECIPIENT USING TECHNIQUE FOR ORDER PERFORMANCE BY SIMILARY TO IDEAL SOLUTIONS (TOPSIS) METHOD (CASE STUDY : KOTAPULU VILLAGE, DOLO DISTRICT) - Syaiful Hendra; Hajra Rasmita Ngemba; Kadek Agus Dwijaya; Herdianto Ladania; Muhammad Aristo Indrajaya (LPPM Universitas Tadulako, 2022)
This study aims to create a decision support system for home renovation aid recipients that can speed up and simplify the decision-making process in providing home surgery assistance so that home surgery assistance is more objective in accordance with community priorities or on target using the TOPSIS method. The TOPSIS method uses the principle that the chosen alternative must have the closest distance from the positive ideal solution and the longest (farthest) distance from the negative ideal solution from a geometric point of view by using the Euclidean distance (distance between two points) to determine the relative proximity of an alternative to the optimal solution. . The criteria used in the system are land ownership, roof conditions, wall conditions and floor conditions. The data used by the author is 210 original data from the Kotapulu village office. so that the system created by the author can make it easier for the Kotapulu village office to determine the recipient of the house renovation assistance only by inputting population data based on the survey results.